Hubungan Tingkat Pengetahuan Orangtua tentang Pencetus Asma dengan Frekuensi Serangan pada Pasien Asma Anak - Puji Rahmawati; Ismiranti Andarini; . Sumardiyono (Nexus Kedokteran Klinik, 2013)
Background: Asthma is a chronic inflammatory airway disease characterized by episodic wheeze, coughe, and tightness in chest due to airway obstruction. Asthma attack is usually preceded by various kinds of triggers and different in each person. Asthma management is very complex and requires collaboration between patient with their families, especially parent. In order to properly manage asthma, patient and parent should have specific knowledge about asthma. This study aimed to determine the association between parent knowledge about asthma triggers and asthma attack frequency in children. Methods: This analytic study was observational using cross sectional approach. The population of this study was child patient with asthma at RSUD Dr. Moewardi Surakarta and Balai Besar Kesehatan Paru Masyarakat. A sample of 33 study subjects was selected by purposive sampling from outpatient and inpatient with asthma who visited Pediatric Clinics, RSUD Dr. Moewardi Surakarta and Balai Besar Kesehatan Paru Masyarakat and suitable with the inclusion criteria. The data was collected by interview using a set of questionnaire from Asthma General Knowledge Questionnaire (AGKQ) and International Study of Asthma and Allergies in Childhood (ISAAC) filled by the parent of patients. The data was analyzed using Chi Square test (?2) on SPSS 17.0 for Windows program. Results: From the analysis of relationship of parent knowledge about asthma triggers and asthma attack frequency on children obtained ?2 count rate of 5.629, p = 0.026, and C = 0,382. The C value indicates level of relationship of parent knowledge about asthma triggers and asthma attack frequency on children is 38,2%. Conclusions: There is a statistically significant relationship of parent knowledge about asthma triggers and asthma attack frequency on children. Keywords: parent knowledge, asthma attack frequency